2016
DOI: 10.1021/acs.jpcc.6b11653
|View full text |Cite
|
Sign up to set email alerts
|

Polyiodide-Doped Graphene

Abstract: Iodine-doped graphene has recently attracted significant interest as a result of its enhanced conductivity and improved catalytic activity. Using density functional theory calculations, we obtain the formation energy, desorption rate, and electronic properties for graphene systems doped with polyiodide chains consisting of 1–6 iodine atoms in the low-concentration limit. We find that I3 and I5 act as p-type surface dopants that shift the Fermi level 0.46 and 0.57 eV below the Dirac point, respectively. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…Since the dissociation of a single I 2 on graphene is clearly unfavorable (+0.74 eV) [17], more molecules should be considered. First, we calculated interaction of four iodine atoms inside a SWCNT and between SWCNTs inside a 064002-2 bundle.…”
Section: A First-principles Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the dissociation of a single I 2 on graphene is clearly unfavorable (+0.74 eV) [17], more molecules should be considered. First, we calculated interaction of four iodine atoms inside a SWCNT and between SWCNTs inside a 064002-2 bundle.…”
Section: A First-principles Calculationsmentioning
confidence: 99%
“…Recent ab initio calculations of graphene doping by iodine suggested that various iodine species should be considered [16,17]. Even though many characterization studies have been conducted on doping processes in CNTs [18][19][20], the mechanism of iodine doping remains a long-debated subject.…”
Section: Introductionmentioning
confidence: 99%
“…

We report the high-pressure structural characterization of an organic polyiodide salt in which ap rogressive addition of iodine to triiodide groups occurs.C ompression leads to the initial formation of discrete heptaiodide units, followed by polymerization to a3Danionic network. [2][3][4] Nowadays,v arious PIs are known, ranging from I 3 À to I 29 3À ,with the general formula I nÀ 2 m+n and n up to 4. [1] Their structural diversity,which is due to the bonding flexibility of iodine,r emains the subject of continuous interest.

…”
mentioning
confidence: 99%
“…In general, the performance of iodine-doped CNT systems may be affected by iodine atom interactions. An example is the presence of iodine in polyiodide form, as described in experimental papers on both CNT [3,49] and graphene [50], which suggest that I À 3 and I À 5 polyiodide chains may be formed during the doping process. An iodine chain structure located inside CNT's was also observed in experiments performed by Fan et al [51].…”
Section: Polyiodide-doped Carbon Nanotubementioning
confidence: 93%